Alternative in vitro models used in the main safety tests of cosmetic products and new challenges - Filaire, Edith; Nachat‐Kappes, Rachida; Laporte, Camille; Harmand, Marie‐Françoise; Simon, Marina; Poinsot, Christian (International journal of cosmetic science, 2022)
Background Guided by ethical considerations and regulatory requirements such as the 7th Amendment to the European Cosmetics Directive N° 1223/2009, the cosmetic industry has developed and evaluated alternative test strategies such as in vitro assays, in silico approaches for toxicological endpoints and efficacy of cosmetic products and cosmetics ingredients. In consequence, the European Centre for the Validation of Alternative Methods (ECVAM) has proposed a list of validated cell‐based in vitro models for predicting the safety and toxicity of cosmetic ingredients. These models have been demonstrated as valuable and effective tools to overcome the limitations of animal in vivo studies. For example, 3D human skin equivalent models are used to evaluate skin irritation potential; and excised human skin is used as the gold standard for the evaluation of dermal absorption. Objective This review presents, in relation to the regulatory requirements, the main alternative in vitro models used in the safety tests of cosmetic products, focusing on skin sensitization, skin corrosion, skin irritation and skin absorption, with advantages and limitations of each model. Recent innovative 3D cell technologies such as Organ‐on‐a‐Chip (OoC) models that can bring significant improvements for toxicology and efficacy testing are also presented. Conclusion The development of OoC technology is promising for assessing the toxicity of substances contained in cosmetics, particularly for repeated dose toxicity, for which no alternative in vitro methods are currently available. Nevertheless, aside from the challenges, the technology needs to be validated and accepted by regulatory organizations as an effective method. Collaboration between researchers, regulatory organizations and industry would be required to achieve this validation. Résumé Contexte Guidée par des considérations éthiques et des exigences réglementaires telles que le 7e amendement à la directive européenne sur les cosmétiques N° 1223/2009, l'industrie cosmétique a développé et évalué des stratégies de test alternatives telles que des tests in vitro, des approches in silico pour les paramètres toxicologiques et l'efficacité des produits cosmétiques et ingrédients cosmétiques. En conséquence, le Centre Européen pour la Validation des Méthodes Alternatives (ECVAM) a proposé une liste de modèles cellulaires in vitro validés pour prédire la sécurité et la toxicité des ingrédients cosmétiques. Ces modèles ont été démontrés comme des outils précieux et efficaces pour surmonter les limites des études animales in vivo. Par exemple, des modèles équivalents de peau humaine 3D sont utilisés pour évaluer le potentiel d'irritation de la peau; et la peau humaine excisée est utilisée comme « gold standard » pour l'évaluation de l'absorption cutanée. Objectif Cette revue présente, en lien avec les exigences réglementaires, les principaux modèles alternatifs in vitro utilisés dans les tests de sécurité des produits cosmétiques, en se concentrant sur la sensibilisation, la corrosion, l'irritation et l'absorption cutanée, avec les avantages et les limites de chaque modèle. Des technologies cellulaires 3D innovantes récentes telles que les modèles Organ‐on‐a‐Chip (OoC) qui peuvent apporter des améliorations significatives pour la toxicologie et les tests d'efficacité sont également présentées. Conclusion Le développement de la technologie OoC est prometteur pour évaluer la toxicité des substances contenues dans les cosmétiques, en particulier pour la toxicité à doses répétées, pour laquelle aucune méthode alternative in vitro n'est actuellement disponible. Néanmoins, outre les défis, la technologie doit être validée et acceptée par les organismes régulateurs comme une méthode efficace. Une collaboration entre les chercheurs, les organismes régulateurs et l'industrie serait nécessaire pour parvenir à cette validation.